Sales Data Analysis and Visualization for Distribution Optimization: Case Study: US Candy Distribution - Riska Indarwati; Herti Yani; Beny, Beny (International Journal of Information Technology and Business, 2025)
Optimization of US Candy's product distribution was conducted through sales data analysis and visualization. The main challenges identified include less strategic factory locations and high logistics costs. This research used a quantitative approach. The purpose of this analysis is to analyze the distribution pattern. Data visualization was conducted using Power BI to show the results of the analysis that New York is the highest selling city with total sales of $10,945.89, with the leading product being Wonka Bar - Scrumdiddlyumptious ($2,718). The consistent increase in sales trend in the fourth quarter of each year, triggered by celebrations such as Halloween, special promotions, and holidays can be utilized to develop future marketing and product inventory strategies. A distribution optimization strategy is recommended to minimize logistics costs and delivery time, by moving distribution to the Wicked Choccy's factory with a distance of 8237.2 km. Marketing strategies such as discounting best-selling products and bundling system for low-selling products are proposed to improve market competitiveness. The resulting interactive dashboard implementation is expected to assist the company in making more accurate and efficient data-based decisions.